2010
DOI: 10.4049/jimmunol.1002517
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-12 Dampens the Immune Response to Malaria Independently of the Inflammasome by Targeting NF-κB Signaling

Abstract: Pathogen sensing by the inflammasome activates inflammatory caspases that mediate inflammation and cell death. Caspase-12 antagonizes the inflammasome and NF-κB and is associated with susceptibility to bacterial sepsis. A single-nucleotide polymorphism (T125C) in human Casp12 restricts its expression to Africa, Southeast Asia, and South America. Here, we investigated the role of caspase-12 in the control of parasite replication and pathogenesis in malaria and report that caspase-12 dampened parasite clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…For instance, caspase-1 is stimulated by Plasmodium-parasitized RBCs (containing hemozoin), but its activity is dispensable during malaria, as Casp1 À/À mice are equivalent to wild-type mice in clearing the P. chabaudi parasite or succumbing to P. bergheiinduced cerebral malaria. 67,68 Similarly, although it was unanimous that the alum adjuvant stimulated the NLRP3 inflammasome in vitro, whether NLRP3 signaling is required for alum's adjuvanticity has been debated. Indeed, although some studies reported abrogation of antibody production in response to antigen in mice lacking the NLRP3 inflammasome, 55,57 others found a partial inhibition 56 or a complete lack of phenotype.…”
Section: Agonists Of the Nlrp3 Inflammasome And Mechanisms Of Activationmentioning
confidence: 99%
“…For instance, caspase-1 is stimulated by Plasmodium-parasitized RBCs (containing hemozoin), but its activity is dispensable during malaria, as Casp1 À/À mice are equivalent to wild-type mice in clearing the P. chabaudi parasite or succumbing to P. bergheiinduced cerebral malaria. 67,68 Similarly, although it was unanimous that the alum adjuvant stimulated the NLRP3 inflammasome in vitro, whether NLRP3 signaling is required for alum's adjuvanticity has been debated. Indeed, although some studies reported abrogation of antibody production in response to antigen in mice lacking the NLRP3 inflammasome, 55,57 others found a partial inhibition 56 or a complete lack of phenotype.…”
Section: Agonists Of the Nlrp3 Inflammasome And Mechanisms Of Activationmentioning
confidence: 99%
“…[107][108][109][110][111][112][113] Caspase-12 has recently emerged as a negative regulator of immune responses in mammals, causing higher susceptibility to colitis, bacterial infection and sepsis. 110,[112][113][114] Mechanistically, caspase-12 can either inhibit caspase-1, dampening the production of pro-inflammatory cytokines 112,114 or suppress the NF-kB pathway, independent of caspase-1 110,115 (Figure 6b). Cellular FLICE-inhibitory protein (cFLIP) is a proteolytically inactive caspase-8 homolog that acts as a dominant-negative inhibitor of caspase-8 in the apoptotic extrinsic pathway of mammals.…”
Section: The Type I Metacaspase Regulatory Module In Hrmentioning
confidence: 99%
“…The absence of caspase-12 thus increased NOD1/2-mediated activation of mitogen-activated protein (MAP) kinase and NF-κB signalling in the gastro-intestinal tract (LeBlanc et al, 2008). Caspase-12 knockout mice were demonstrated to clear the malaria parasite Plasmodium chabaudi better than control mice because of increased cytokine production in the absence of caspase-12 (Labbe et al, 2010). This was not because of enhanced inflammasome and NOD1/2 signalling, but rather because NF-κB activation was increased in the absence of caspase-12-mediated sequestration of the central NF-κB modulator IκB kinase (IKK)γ/NEMO (Labbe et al, 2010).…”
Section: Caspase-12: a Negative Regulator Of Immune Signallingmentioning
confidence: 95%
“…Caspase-12 knockout mice were demonstrated to clear the malaria parasite Plasmodium chabaudi better than control mice because of increased cytokine production in the absence of caspase-12 (Labbe et al, 2010). This was not because of enhanced inflammasome and NOD1/2 signalling, but rather because NF-κB activation was increased in the absence of caspase-12-mediated sequestration of the central NF-κB modulator IκB kinase (IKK)γ/NEMO (Labbe et al, 2010). Caspase-12 also was shown to contribute to effective host defence responses against West Nile Virus (WNV) infection by enhancing type I interferon production by the intracellular RNA receptor RIG-I (Wang et al, 2010).…”
Section: Caspase-12: a Negative Regulator Of Immune Signallingmentioning
confidence: 99%